Effects of Tobacco and Alpha Lipoic Acid Treatment on Puberty Parameters in Male Rats - Yardimci, Ahmet; Ulker, Nazife; Tektemur, Ahmet; Kaya, Nalan; Guzel, Elif Erdem; Akkoc, Ramazan Fazil; Ozan, Enver (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY